2018
DOI: 10.1111/ene.13830
|View full text |Cite
|
Sign up to set email alerts
|

Early thrombosis prophylaxis with enoxaparin is not associated with hematoma expansion in patients with spontaneous intracerebral hemorrhage

Abstract: Background and purpose Early pharmacological deep vein thrombosis (DVT) prophylaxis is recommended by guidelines, but rarely started within 48 h. We aimed to analyze the effect of early (within 48 h) versus late (>48 h) DVT prophylaxis on hematoma expansion (HE) and outcome in patients with spontaneous intracerebral hemorrhage (ICH). Methods We analyzed 134 consecutive patients admitted to a tertiary neurointensive care unit with diagnosed spontaneous ICH, without previous anticoagulation, severe coagulopathy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…After scanning titles and abstracts, 444 citations were excluded and 21 were retained for further evaluation. From these, 11 studies were excluded for the following reasons: 9 studies did not have a control group [3-21]; one study used vitamin K antagonists [22]; and in one study treatment was given during rehabilitation after 7 days from stroke onset [23]. One further randomized study [24] was excluded because the results of this trial had been included in the results of the study reported by Boeer et al [25].…”
Section: Resultsmentioning
confidence: 99%
“…After scanning titles and abstracts, 444 citations were excluded and 21 were retained for further evaluation. From these, 11 studies were excluded for the following reasons: 9 studies did not have a control group [3-21]; one study used vitamin K antagonists [22]; and in one study treatment was given during rehabilitation after 7 days from stroke onset [23]. One further randomized study [24] was excluded because the results of this trial had been included in the results of the study reported by Boeer et al [25].…”
Section: Resultsmentioning
confidence: 99%
“…This study has certain clinical significance for neurointensive care unit medical staff and patients: early administration of anticoagulants remains a controversial issue, as some researchers have indicated that early pharmacological prophylaxis increases the risk of bleeding (20,21), whereas others argued that early use of anticoagulants is not associated with late bleeding (22,23); furthermore, there are no clear guidelines for the application of anticoagulants in neurointensive care unit patients with different diagnoses; however, the prognostic nomogram model may assist neurosurgeons in the early identification of high-risk patients to provide them with active individual anticoagulant treatment after cautious assessment of thrombosis vs. bleeding.…”
Section: Discussionmentioning
confidence: 98%
“…46 These results are supported by a prospective observational study demonstrating the absence of hematoma expansion with LMWH started within 48 h of ICH onset after hematoma stabilization compared to later initiation in 134 consecutive patients. 47 Similarly, in another observational study of 407 ICH patients, there was no increase in ICH expansion between those treated with LMWH (85% started within 48 h) or those receiving no chemoprophylaxis. 48 Following ICH, patients are at increased risk of seizures.…”
Section: Presentationmentioning
confidence: 89%